MENGURAI DAMPAK DIGITAL : TRANSFORMASI HUKUM BISNIS SYARIAH DI ERA EKONOMI DIGITAL - Nadya, Anandhita; Tartila, Lisana; Sari, Nabila; Putri, Venotty Ananda (Taksasila Edukasi Insani, 2025)
The digital revolution has transformed the global economy, with the use of information and communication technology. These changes have had an impacts on Sharia law. This research analyze the effect of digital transformation on Sharia business law, identifies challenges such as the validity of electronic contracts and transactions, and explores the potetial adaptation of sharia e-commerce and fintech. Qualitative methods, were used with literature analysis. The findings show that digital transformation offers opportunities and challenges for Sharia law. Adaptation strategies, digital literacy,strong technological infrastructure, and a responsible development Sharia Fintech are important to maintain therelevance of Sharia law in fair transactions. The study concludes that an appropriate response will empower Sharia law in creating an inclusive digital economic ecosystem as per Islamic principles.Keywords : Digital transformation, Sharia business law, Digital economy era